Lapak Jeneponto: Designing an Inclusive Mobile Marketplace UI for MSMEs in Rural Indonesia - Suci Ramadhani Arifin; Sriwahyuningsih Piu (Turast: Jurnal Penelitian dan Pengabdian, 2025)
Jeneponto Regency's MSMEs face significant challenges accessing wider markets despite their economic potential. This research designed a User Interface (UI) for a mobile marketplace application ("Lapak Jeneponto") to enhance product visibility and market reach for local MSMEs. Using the Google Design Sprint methodology, we identified key user needs, generated features, created prototypes, and validated designs with 15 participants representing both MSME owners and potential customers. The prototype features product catalog, shopping cart, and payment functionality addressing four identified challenges: limited market information, low product visibility, restricted customer base, and inadequate digital literacy. Validation testing revealed strong preferences (92%) for Indonesian language interfaces, high task completion rates (87%), and demand for Cash on Delivery payment options. The resulting user-friendly interface accommodates varying digital literacy levels and aims to unlock growth opportunities for local businesses, contributing to regional economic development.